Mammalian energetic savings in subterranean environment. The case of African mole-rats. - Okrouhlík, Jan (Jihočeská univerzita, 2014)
Mole-rats are placental mammals which are perfectly adapted to subterranean life. In this thesis I present novel findings on working metabolism and thermoregulatory physiology of mole-rats. These animals cope with low availability of food and have thus employed multiple strategies how to conserve energy and/or use it more effectively. Among other adaptations this resulted in lower resting body temperature, tolerance to increase in body temperature during exercise or while at rest, surprisingly efficient cooling while digging and precise diurnal and seasonal timing of activity with regards to environmental conditions. My focus in this work is on the digging metabolic rate and thermoregulation of social Fukomys mechowii and solitary Heliophobius argenteocinereus in soft and hard substrate, thermoregulatory abilities of Fukomys darlingi, seasonal changes of activity in free living Heliophobius argenteocinereus measured as daily energy expenditure and, finally, energetic consequences of the daily activity patterns of Fukomys anselli.
Mammalian energetic savings in subterranean environment. The case of African mole-rats.
Keywords: metabolismus; termoregulace; Heliophobius; Fukomys; rypoši; pracovní metabolismus; energetické úspory; metabolism; thermoregulation; Heliophobius; Fukomys; mole-rat; working metabolic rate; resting metabolic rate